Phylogenetic Relationships of Selected Raja Banana (Musa × paradisiaca L.) Cultivars from Java Based on Chloroplast rbcL Sequences and Their Implications for Germplasm Conservation - Ahmad Affan Ali Murtadlo; Pablo A Valverde Pérez; Loreiny Garcia (Cahaya Ilmu Cendekia Publisher, 2025)
Purpose of the study: This study aimed to investigate the phylogenetic relationships, genetic variation, and geographic distribution patterns of Raja banana (Musa × paradisiaca L.) cultivars distributed across Java Island using chloroplast rbcL gene sequences and to provide molecular information supporting germplasm conservation and sustainable management of banana genetic resources in Indonesia. Methodology: Young leaf samples of seven Raja banana cultivars were collected from Java Island. Genomic DNA was extracted using the Wizard® Genomic DNA Purification Kit (Promega, USA). The chloroplast rbcL gene was amplified by PCR and sequenced by First BASE Laboratories (Malaysia). Sequence alignment was performed using ClustalX v2.1. Genetic diversity was analyzed with DnaSP v6.12.03, phylogenetic reconstruction with MEGA v6.0, haplotype network analysis with Network v5.0, and tree visualization with FigTree v1.4.3. Main Findings: The rbcL sequences showed high conservation with limited nucleotide variation among cultivars. Of the 553 nucleotide positions analyzed, 11 variable sites were detected, resulting in two haplotypes with haplotype diversity (Hd) of 0.571 and nucleotide diversity (π) of 0.0043. Maximum Likelihood phylogenetic analysis grouped the cultivars into two major clades, indicating close evolutionary relationships among the examined cultivars. Haplotype network analysis supported the phylogenetic structure and revealed distinct genetic groupings among cultivars distributed across Java Island. Novelty/Originality of this study: The integration of chloroplast rbcL-based phylogenetic analysis with geographic distribution interpretation to investigate Raja banana cultivars across Java Island. This research evaluates phylogenetic relationships, haplotype structure, and cultivar distribution patterns, providing additional insights into the conservation of Indonesian banana germplasm.